2018
DOI: 10.1016/j.tvjl.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A review of treatment options for behavioural manifestations of clinical anxiety as a comorbidity in dogs with idiopathic epilepsy

Abstract: Psychiatric comorbidities affect a large percentage of people with epilepsy and have a detrimental impact on their quality of life. Recently, behavioural comorbidities, with similar characteristics to human psychiatric diseases, have been identified in dogs with idiopathic epilepsy. In particular, behaviours motivated by the fear-anxiety emotional system have been found to be associated with the occurrence of idiopathic epilepsy in both dogs receiving anti-epileptic drugs, and drug-naïve dogs. There has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 117 publications
(118 reference statements)
0
26
0
Order By: Relevance
“…In humans, several and an increasing number of studies have identified a bi-directional relationship between psychiatric disorders and recurrent seizure disorders [62][63][64][65][66]. This co-morbidity has also been reported in laboratory rats [67,68] and companion dogs [69,70]. Depression and anxiety disorders, followed by psychoses and attention deficit disorders, are the most common psychiatric disorders in human medicine.…”
Section: Abnormalities In Laboratory or Imaging Work-up Examplesmentioning
confidence: 93%
“…In humans, several and an increasing number of studies have identified a bi-directional relationship between psychiatric disorders and recurrent seizure disorders [62][63][64][65][66]. This co-morbidity has also been reported in laboratory rats [67,68] and companion dogs [69,70]. Depression and anxiety disorders, followed by psychoses and attention deficit disorders, are the most common psychiatric disorders in human medicine.…”
Section: Abnormalities In Laboratory or Imaging Work-up Examplesmentioning
confidence: 93%
“…In addition to seizure control, there is an emerging need for therapies for co-morbid anxiety in dogs with epilepsy. Increases in anxiety following the onset of epilepsy have been documented in dogs with epilepsy (2); however, in a recent review on psychopharmacological options for the treatment of anxiety in dogs with IE, it was concluded that there is a scarcity of evidence of the effects of standard anxiolytic therapies in the IE population, with many drugs having pharmacokinetic interactions with AEDs, or contraindicated in these patients (50). Furthermore, patient response to anxiolytic medications may differ between healthy brains and epileptic brains.…”
Section: Is There a Need For Behavioral Therapy In Canine Epilepsy Pamentioning
confidence: 99%
“…In a recent study, 1 in 10 owners of epileptic dogs that were using dietary supplements reported that their aim was to improve behavioral problems associated with epilepsy (16). The use of behavioral therapy has been advocated in this population (50); however, its efficacy has yet to be ascertained with controlled trials, or indeed reported in case reports or series as yet.…”
Section: Is There a Need For Behavioral Therapy In Canine Epilepsy Pamentioning
confidence: 99%
“…Moreover, the prevalence of major depression occurs more frequently in patients with epilepsy (28). Behavioral changes due to an epileptic cause (23,29) and its impact on quality of life are also in veterinary medicine a topic of increased interest (30). In the current study, an association between behavioral changes and epilepsy could be detected within group one.…”
Section: Discussionmentioning
confidence: 50%